Forms of address : the case of University of Limpopo - Malatji, Rebecca Ntshwaki (My University, 2022)
The aim of this study was to explore the forms of address and terms of reference used by students to address their lecturers at the University of Limpopo. The study discovered that, there were many ways in which forms of address and terms of reference are used. The theory of pronouns of power and solidarity by Brown and Gilman (1960) is implemented. Data are collected using face-to-face and telephone interviews from a sample of fifteen (15) University of Limpopo postgraduate students majoring in languages and linguistics in Turfloop, Limpopo, South Africa, however, ten (10) participants satisfied the notion of data saturation. This is because the participants were giving slightly similar information. The study found that there are two types of forms of address which are used by the University of Limpopo students which are Names and Titles. Addressing lecturers by first name, last name, nickname or title plus first name symbolises closer relationship between student and lecturers whereas, addressing lecturers by title only or title plus last name represents a limited relationship between the lecturer and student. It is found that most of postgraduate students address lecturers depending on the relationship existing between them and the lecturers. It has been found that, the factors that influence choice of forms of address are setting, respect, degree of intimacy, age and culture; and factors that influence the use of terms of reference are setting and respect. The data obtained reveal that undergraduate students, especially first years are not aware of the importance of forms of address. And it has been found that students promote the idea of the implementation of a rule(s) or policy regarding the importance of forms of address.
Thesis(M.A.(Translation Studies and Linguistics)) -- University of Limpopo, 2022
Keywords: Terms of reference; Students; Pronouns; University of Limpopo; English language -- Address, Forms of; Forms of address; Language and languages; College students -- South Africa -- Limpopo